The Future of Occupational Health: Anticipating Risks in the Evolving Workplace - Parsakia, Kamdin; Seyed Ali Tabar, Seyed Hadi (Journal of Foresight and Health Governance, 2024)
This study aims to examine emerging occupational health risks in evolving workplace environments and explore strategic interventions to enhance worker well-being, safety, and resilience. A narrative review using a descriptive analysis method was conducted to synthesize recent literature on occupational health challenges, including technological advancements, workplace transformations, and psychosocial risks. Sources published between 2020 and 2025 were reviewed from peer-reviewed journals, policy reports, and health organization databases. The study focused on three primary dimensions: physical risks, psychosocial risks, and environmental and biological hazards. Additionally, policy and regulatory considerations were analyzed to assess gaps and future recommendations for workplace health protections. The study highlights the impact of automation, artificial intelligence, and digitalization on occupational health, identifying increased cognitive workload, digital fatigue, and workplace stress as critical emerging risks. The rise of remote work and gig-based employment has led to concerns regarding ergonomic health, social isolation, and job insecurity. Additionally, climate change and emerging pathogens pose significant health threats to workers in various industries. Current occupational health regulations fail to comprehensively address these challenges, particularly in non-traditional employment settings. Advances in workplace health strategies, including AI-driven health monitoring, flexible work policies, and mental health support programs, show promise in mitigating risks, but their ethical implementation requires careful regulatory oversight. Occupational health risks are evolving alongside technological and workplace transformations, necessitating proactive policies, employer-driven interventions, and enhanced regulatory frameworks. Addressing these challenges requires a multidisciplinary approach that integrates workplace safety, mental health support, and ethical AI governance. Future research should focus on the long-term effects of automation and climate-related occupational risks, ensuring that workplace health policies remain adaptive and inclusive.